A genomic biomarker that identifies human bone marrow-derived mesenchymal stem cells with high scalability. (8th June 2020) - Sathiyanathan, Padmapriya; Samsonraj, Rebekah M.; Tan, Clarissa L. L.; Ling, Ling; Lezhava, Alexander; Nurcombe, Victor; Stanton, Lawrence W.; Cool, Simon M.
Abstract: Although the application of human mesenchymal stem cells (hMSCs) to repair damaged or diseased tissues has proven relatively effective, both the donor-to-donor variability in ex vivo expansion rates and the maintenance of stemness remain a bottleneck to widespread translation. Previous work from this laboratory stratified donors into those yielding hMSCs with high- or low-growth capacity; global transcriptomic analysis revealed that high-growth-capacity hMSCs were characterized by a loss of the gene encoding glutathione S-transferase theta 1 ( GSTT1 ). These GSTT1 -null hMSCs demonstrated increased proliferative rates, clonogenic potential, and longer telomeres compared with low-growth capacity hMSCs that were GSTT1- positive. Thus, this study identifies GSTT1 as a novel genomic DNA biomarker for hMSC scalability. : Abstract : GSTT1 is a novel genomic biomarker of human mesenchymal stem cell (hMSC) scalability. GSTT1 -null ( GSTT1*0/*0 ) hMSCs possess higher clonogenicity and proliferative capacity in comparison to homozygous positive ( GSTT1*1/*1 ) cells.